Analisis Peran Trend Fashion dan Fear of Missing Out terhadap Keputusan Pembelian Produk Von Dutch pada Mahasiswa-Mahasiswi - Fikri Kamilia Ikhwanda; Giyana Giyana (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The rapid growth of the fashion industry has significantly influenced consumer behavior, especially among university students. This study examines the role of fashion trends and Fear of Missing Out (FoMO) in purchasing decisions for Von Dutch products among students. Using a qualitative approach through literature review, the research integrates insights from academic sources to analyze these phenomena. Findings reveal that fashion trends create a sense of identity and belonging, while FoMO drives impulsive purchasing behavior due to social and emotional pressures. The combination of these factors significantly impacts students’ decisions to buy Von Dutch products, highlighting the importance of nostalgia-driven marketing strategies. These results provide valuable insights for marketers targeting young consumers.